Frontières nationales et aménagement : Paradoxes territoriaux en France et dans l’Union européenne - Grégory Hamez (Bulletin de l’Association de Géographes Français)
The territorial issues of planning know no borders, but spatial planning is a practice organized above all according to national traditions, following spheres of competence compartmentalized at the borders. The article proposes a definition of what planning in a cross-border context covers in the European Union, whether it involves the setting up of observatories, the development of joint strategies or the construction of facilities. The disjunction between different approaches to planning on each side of the border makes this type of planning eminently paradoxical, even when the objectives are shared. The paper gives various examples of this, particularly in terms of sustainable development and participation.